Strategi Komunikasi dalam Hubungan Jarak Jauh: Studi Fenomenologi pada Pasangan Long Distance Relationship (LDR) - Azizah, Sayidatul (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2025)
Long-distance relationships (LDR) are becoming an increasingly common phenomenon in modern social dynamics, especially with the development of communication technology. This study aims to analyze the communication strategies used by couples in LDR relationships to maintain emotional closeness, resolve conflicts, and maintain relationships. This study uses a phenomenological approach with qualitative methods, where data is obtained through in-depth interviews with couples who have undergone LDR for a certain period of time. The results of the study indicate that LDR couples implement various communication strategies, such as routine communication through digital media, use of affectionate language, emotional openness, and the use of interactive technology such as video calls and voice messages. In addition, trust and commitment are important factors in maintaining relationship stability. Although challenges such as limited physical interaction and time zone differences are obstacles, effective communication strategies can help couples build harmonious relationships. This study provides insights for couples undergoing LDR as well as implications for the development of interpersonal communication theory in the context of long-distance relationships.